Structural Factors Underlying Medical Malpractice: From the Perspective of Social Science Experts and Medical Specialists - simin kazemi (Journal of Qualitative Research in Health Sciences, 2021)
Introduction: Medical malpractice is generally attributed to the lack of individual competence of physicians, but from a sociological point of view, it is a problem that arises in a social context influenced by external factors and variables. The purpose of this study was to determine the structural factors that underlie the formation of medical malpractice.Methods: This qualitative study was conducted using the content analysis method in 2018. The research population consisted of practitioners and experts in the fields of medicine and social sciences in Iran. The participants were selected using purposive sampling and the sample size was determined based on the theoretical saturation. The data were collected through interviews with a total of 13 experts who participated in the study. The data from the interviews were transcribed and the data were analyzed using a content analysis method to extract related categories and subcategories.Results: Based on the data analysis, 24 subcategories and 6 main categories including the political economy of health, healthcare system problems, the position of physicians in the socioeconomic structure, weak supervision on physicians, undesirable quality of medical education, and the role of physicians’ civil liability insurance were identified as the structural factors accounting for medical malpractice in Iran.Conclusion: Structural reform of the healthcare system, provision of amenities, facilities, and human resources, reconsidering the power of physicians by modifying the physician-patient relationship and taking into account patients’ rights, careful and scientific supervision of physicians’ performance, accepting the necessity of medical transparency, improving the quality of medical education, and finally the resolution of the contradiction in the role of civil liability insurance of physicians can be used by health policymakers and decision-makers in planning to prevent medical malpractice.